3(-4x+1)=-12x-5

Simple and best practice solution for 3(-4x+1)=-12x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-4x+1)=-12x-5 equation:


Simplifying
3(-4x + 1) = -12x + -5

Reorder the terms:
3(1 + -4x) = -12x + -5
(1 * 3 + -4x * 3) = -12x + -5
(3 + -12x) = -12x + -5

Reorder the terms:
3 + -12x = -5 + -12x

Add '12x' to each side of the equation.
3 + -12x + 12x = -5 + -12x + 12x

Combine like terms: -12x + 12x = 0
3 + 0 = -5 + -12x + 12x
3 = -5 + -12x + 12x

Combine like terms: -12x + 12x = 0
3 = -5 + 0
3 = -5

Solving
3 = -5

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

 

See similar equations:

| (1.6*x)-3.38=(5.8*x)+4.67 | | 8p^2+8p=-7p^2-3p+14 | | 2/5(h)=8 | | 4x=36-2x | | 8x=22-3x | | j-14=-8 | | X^2+2x=-3x^2+2x+36 | | 5x+8=98-4 | | -2.3x+3.1=4.3x-5 | | (x-5)(x-2+3i)(x+2+3i)=0 | | 4x+13x+2= | | (a+b)x=27 | | x/5-10=2 | | ab+2c=8 | | -y^2-2y+30=0 | | 5x+3(-4x*4x+6)-3x+1=17 | | 402-15x=237 | | 4m=92 | | 0=-y^2-2y+30 | | 103-6x=12x+15 | | 46-4x=5x+24 | | 12mn+o=6k | | 0=-y^2-2y-40 | | 4x+6x-10=60 | | 6-9y=12y | | -29.2=1.7n+5.8+5.3 | | -4(5n+7)=24-7n | | 3x+18=-8 | | 5x+12-2x=27 | | 3y-89=180 | | y=x^3-10x^2+35x-27 | | 2x[3x-(4x-1)]=8x | | 3x+18=-8(-4x+5) | | 8n+5=3-4n | | -7(-5-8m)=-4m+35 | | 2(x)=57 | | -7v-31=-(v+7) | | rt=y+2n | | 8-3(2x-5)=15-2x | | 2(j)+3=17 | | j+2(j)+j-3=17 | | -5x+12=-7(-2x+1) | | 5s+24=14 | | 3x+8=2x+12 | | 3x(4-5)=16 | | j+2(j)+(j-3)=17 | | x^2+16x-13=0 | | 4(x-3)=4x+19 | | 8y+x+32=0 | | 3y=8y+60 | | -12=-3+y | | -4t=48 | | 28+k=-6 | | -16=z+4 | | -3x-4=32 | | 9x+5=x-3 | | 25+h=-23 | | z+7=-6 | | d-4=-2 | | 3x^2+4x=2 | | 3(5-2x)=-(x+1)+41 | | x/14=10/7 | | x+7=-16 | | j+18=52 | | -52=z-12 |